Compliance of public dental clinics in the Umgungundlovu district with norms and standards in the Primary Health Care Package for South Africa - Rajcoomar, Nuerisha (University of the Western Cape, 2016)
Magister Scientiae Dentium - MSc(Dent) === BACKGROUND: The majority of South African citizens are dependent on the State Health Care system for their wellbeing. Dental services are part of this system. The first line of intervention for oral disease is the primary oral health services. The National Norms and Standards for Primary Health Care sets out in detail the services to be offered by state dental clinics. This document also lists the equipment and materials that public dental clinics should be furnished with in order to deliver prescribed services. Despite this, most public dental clinics do not deliver the full spectrum of services due to the lack of materials and equipment. The end result is that patients do not receive the ideal treatment and treatment choices are based on the availability of equipment and material instead of clinical appropriateness. There was a need to determine to what extent the primary oral health clinics comply with the National Norms and Standards for Primary Health Care. The launch of the green paper of the National Health Insurance in 2011 stated that the NHI is a tool to ensure that healthcare to the entire South African population is of an equal standard. The Umgungundlovu District is one of the sites identified as a pilot district for the NHI. Prior to 1994 there was a two tiered health system in South Africa, the private health system and the public health system. It is this historical model that has shaped the current system. It was the socio-economic status of an individual that dictated within which of the two tiers treatment was sought. AIM: To determine whether public dental clinics in the Umgungundlovu District are equipped to deliver the oral health services prescribed by the Primary Health Care Package for South Africa protocol. METHODOLOGY: A cross sectional study was conducted in the Umgungundlovu district which is in KwaZulu Natal to establish which of the prescribed dental services are offered at the clinic. There are 11 dental clinics in the Umgungundlovu District and one mobile dental clinic. All clinics and the mobile clinic were included in the study. Physical inspection and a checklist were used to determine which equipment and materials were available at dental clinics of the Umgungundlovu district and to determine compliance with the National Norms and Standards for Primary Health Care. RESULTS: Dental services were provided at all the 12 dental facilities in the Umgungundlovu district. None of the clinics had 100% of required instruments, materials and equipment. Half of the clinics had more than 50% of required instruments, materials and equipment. Tooth-brushing programs and fluoride mouth rinsing programs were offered by 41.67% of the clinics, fissure sealant applications by 66.67% and topical fluoride application by 25% of the clinics. In addition, while all offered oral examination and emergency pain and sepsis care (including extractions) only half were able to take bitewing radiographs, 58.33% to carry out simple fillings of 1-3 tooth surfaces, 66.67% to provide atraumatic restorative treatment (ART). CONCLUSION: Lack of materials, instruments and equipment, the irregular supply of materials, instruments and equipment and the late supply of materials, instruments and equipment was found to limit the dental treatment offered by the clinics. None of the 12 clinics in the Umgungundlovu district were found to be compliant with the Primary Health Care Package for South Africa – a set of norms and standards document. Availability of dental services was limited in the dental clinics, except at the Edendale Dental Hospital Department